Міграція українських вчених до Польщі в умовах російсько-української війни (на матеріалах усноісторичних джерел) - Шевелєва, Аліна Олексіївна (Харків : Харківський національний університет імені В. Н. Каразіна, 2023)
Робота присвячена вимушеній міграції українських науковців до Польщі в умовах російсько-української війни після 24 лютого 2022 року і є частиною усноісторичного наукового проєкту «Рух на Захід: українські вчені в умовах вимушеної міграції (2014–2023)» (автори – В. Іващенко та Ю. Кісельова). Метою проєкту є дослідження зміни стратегій виживання та побудови карʼєри істориками-мігрантами в екстремальних умовах та визначення рівня солідарності і співпраці всередині європейської академічної спільноти. Інтерв’ю, які були взяті на території Польщі складають значну частину (18 з 46), що дозволяє аналізувати відповідний комплекс як окреме явище в сучасній інтелектуальній міграції. У першому розділі аналізується комплекс усноісторичних джерел, з’ясовуються проблеми авторства, мотиви участі респондентів у проєкті, час, місце та обставини інтерв’ювання, проблеми суб’єктивності. У другому розділі розглядаються осмислення українськими та польськими респондентами процесу міграції українських учених до Польщі, зокрема розглядається сприйняття респондентами початку війни, визначаються фактори, які вплинули на від’їзд, характеризується процес адаптації до нових умов, форми допомоги українським біженцям з боку польських науковців, мотиви цієї допомоги та рефлексія про новий досвід.

The thesis is devoted to the forced migration of Ukrainian scientists to Poland in conditions of the Russian-Ukrainian war after February 24, 2022 and is part of the oral history research project “Moving West”: Ukrainian Academics in Conditions of Forced Migration (2014 – 2023)" (authors: V Ivashchenko and Y. Kiselyova). The aim of the project is to study the change of survival and career building strategies of migrant historians in extreme conditions and to determine the level of solidarity and cooperation within the European academic community. Interviews that were taken on the territory of Poland make up a significant part (18 out of 46), which allows us to analyze the relevant complex as a separate phenomenon in modern intellectual migration. A complex of oral history sources is analyzed in the first chapter, problems of authorship, motives of the respondents' participation in the project, time, place and circumstances of the interview, problems of subjectivity are clarified as well. The second chapter examines Ukrainian and Polish respondents' understanding of the process of Ukrainian scientists migration to Poland, in particular, the respondents' perception of the beginning of the war is considered, factors that influenced the departure are determined, process of adaptation to new conditions, forms of assistance to Ukrainian refugees from Polish scientists, motives of this help andreflection on new experience are characterised.
Migration of Ukrainian Scientists to Poland during Russian Ukrainian War (based on Oral Historical Sources)
Керівник: Іващенко Вікторія Юріївна,кандидат історичних наук, доцент кафедри історіографії, джерелознавства та археології
Keywords: HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; SOCIAL SCIENCES::Social sciences::Education; Польща; українські наукові мігранти; інтелектуальна міграція; усно-історичний проєкт; iнтерв’ю; Poland; Ukrainian scientific migrants; intellectual migration; oral history project; interview